2014
DOI: 10.1371/journal.pone.0091848
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Mitochondria-Shaping Proteins Opa-1 and Drp-1 in Manganese-Induced Apoptosis

Abstract: Mitochondria are dynamic organelles that undergo fusion and fission processes. These events are regulated by mitochondria-shaping proteins. Changes in the expression and/or localization of these proteins lead to a mitochondrial dynamics impairment and may promote apoptosis. Increasing evidence correlates the mitochondrial dynamics disruption with the occurrence of neurodegenerative diseases. Therefore, we focused on this topic in Manganese (Mn)-induced Parkinsonism, a disorder associated with Mn accumulation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 66 publications
4
50
0
Order By: Relevance
“…The activity of Drp-1 regulates mitochondrial fragmentation, and inhibition of it decreases mitochondrial fission and apoptosis (25)(26)(27)42). Drp-1 is crucially involved in the induction of mitochondrial fission, apoptotic cell death, and neurodegeneration (38 -41, 46) through its translocation from the cytosol to mitochondria (34,41,42). Studies suggested that autophagy is critically involved in the control of Drp-1 levels (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The activity of Drp-1 regulates mitochondrial fragmentation, and inhibition of it decreases mitochondrial fission and apoptosis (25)(26)(27)42). Drp-1 is crucially involved in the induction of mitochondrial fission, apoptotic cell death, and neurodegeneration (38 -41, 46) through its translocation from the cytosol to mitochondria (34,41,42). Studies suggested that autophagy is critically involved in the control of Drp-1 levels (35).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ethanol, a well established neurotoxicant also induced mitochondrial fission through enhanced Drp-1 mitochondrial translocation (56). In addition, manganese disrupted the mitochondrial network toward to an exacerbated fragmentation by enhancing the levels of Drp-1 (41,57). Inhibition of excessive mitochondrial fission reduces aberrant autophagy and prevents neurodegeneration (58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial fusion is mediated by Mitofusin 2 and OPA1, 17,18 and its fission is regulated by dynamin-related protein (DRP1). 19 Mitochondrial fission and fusion balance is essential for maintaining the stability of its structure and function. When mitochondrial balance disorders, especially in divided state, mitochondrial membrane potentially decreases, membrane permeability increases, ROS is produced, ATP generation goes down and a large number of apoptotic factors are released.…”
Section: Introductionmentioning
confidence: 99%